Russia (Moscow) 1999 Global Youth Tobacco Survey : Economic Aspects - Ross, Hana (World Bank, Washington, DC, 2013)
The Global Youth Tobacco Survey (GYTS), supported by the US Centers for Disease Prevention and Control and the World Health Organization, was carried out in Moscow in 1999. Russia was one of the first of many countries to implement this standardized school-based survey of teenage smoking behavior, attitudes and knowledge. This report presents background information on smoking and tobacco control policies in Russia. It presents simple descriptive statistics of the GYTS survey data, focusing especially on the relationship between smoking behavior, cigarette prices, and other factors that can be affected by policies intended to reduce smoking, to reduce associated disease and premature deaths. Multiple regressions explore the factors that affect the decision to smoke, and the number of cigarettes that current smokers report smoking each month. The estimates suggest that higher prices are associated with lower smoking prevalence and fewer cigarettes smoked each month. Other factors with a statistically significant effect (increasing smoking) are: age, being male, owning cigarette promotional items and having been offered free cigarettes by cigarette company representatives. Seeing counter-advertising was also statistically significant and associated with less smoking.